2002
DOI: 10.1074/jbc.m207962200
|View full text |Cite
|
Sign up to set email alerts
|

The 2.2-Å Crystal Structure of Human Pro-granzyme K Reveals a Rigid Zymogen with Unusual Features

Abstract: Granzyme K (GzmK) belongs to a family of trypsin-like serine proteases localized in electron dense cytoplasmic granules of activated natural killer and cytotoxic T-cells. Like the related granzymes A and B, GzmK can trigger DNA fragmentation and is involved in apoptosis. We expressed the Ser 195 3 Ala variant of human proGzmK in Escherichia coli, crystallized it, and determined its 2.2-Å x-ray crystal structure. Pro-GzmK possesses a surprisingly rigid structure, which is most similar to activated serine protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 57 publications
1
66
0
Order By: Relevance
“…Recombinant GzmF was expressed in E. coli and refolded from inclusion bodies as previously described. 19 The inactive counterpart, Ser195AlaGzmF (S-AGzmF), was generated by a point mutation of the active site, Ser 195, to Ala. The Gzms were purified with nickel chelation columns, followed by cation exchange chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant GzmF was expressed in E. coli and refolded from inclusion bodies as previously described. 19 The inactive counterpart, Ser195AlaGzmF (S-AGzmF), was generated by a point mutation of the active site, Ser 195, to Ala. The Gzms were purified with nickel chelation columns, followed by cation exchange chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins were expressed and refolded from Rosetta (DE3) (Novagen, Darmstadt, Germany) inclusion bodies as described. 19 After thoroughly washing and refolding for 3 days, proteins were harvested and activated by enterokinase treatment. The enterokinase was removed and GzmF was purified on a Hitrap ion exchange column (Amersham Biosciences, Pittsburgh, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…GzmK, like GzmA and GzmB, is synthesized as a zymogen precursor, containing a signal and a short propeptide preceding the mature polypeptide chain [15]. GzmK and GzmA differ from GzmB by their substrate specificity [5]. The study showed that GzmA-deficient CTLs still contain 20% tryptase activity and their cytolytic activity is just slightly reduced [16], suggesting that GzmK might be a potent Gzm to rescue the GzmA activity.…”
Section: Introductionmentioning
confidence: 96%
“…Gzms belongs to a family of serine proteases (SPs) localized in the electron dense cytoplasmic granules of activated NK and Tc cells [5]. Gzm loci have been placed into three groups by their chromosomal location and structural similarities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation